Anaerobic Exercise Training in the Therapy of Substance Use Disorders: A Systematic Review - Colledge, Flora; Gerber, Markus; Pühse, Uwe; Ludyga, Sebastian (Frontiers in Psychiatry, 2018)
Background In the past three decades, there has been an increase in the number of studies assessing exercise as a form of treatment for substance use disorders (SUDs). While a variety of substance types and outcomes have been assessed, exercise intensities have never been systematically examined. Consequently, it remains unclear whether particular forms of exercise are better suited to the treatment of these populations. Anaerobic exercise has been shown to have positive effects in populations with psychiatric disorders, but its effectiveness in the treatment of SUDs has to date not been reviewed. Methods The aim of this systematic review is to identify and evaluate studies which have employed either an acute or chronic anaerobic exercise component as a therapy modality for SUDs. The primary outcomes are abstinence, craving, withdrawal, consumption, quality of life, and the following psychological symptoms and disorders: depression, anxiety, stress, and mood. A secondary objective is to assess whether the type of training described in the study protocol can be reliably categorised as anaerobic training. Results Twenty-six studies are included in this review. Twelve studies addressed nicotine dependence, one addressed alcohol dependence, and thirteen addressed dependence on various illicit drugs. Thirteen studies reported the intensity at which participants actually exercised, but only one employed a test to determine whether training was carried out above the anaerobic threshold. The risk of bias in the included studies was generally high. Results of the studies were mixed, with the most positive effects being found for abstinence in nicotine dependence. Conclusion The evidence for the effects of anaerobic exercise in SUDs is weak, although a tendency towards positive effects on abstinence in nicotine dependent individuals was observable. The majority of studies do not report data on exercise intensity, making a categorisation of anaerobic exercise impossible in all but one case. This means that the effects of this form of exercise cannot be determined, and therefore not evaluated or compared with other forms. In order to improve the quality of evidence for exercise in SUD treatment, clearly defined and objectively assessed evaluations of anaerobic and anaerobic exercise are necessary.